Two new species of Turleania McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the Ryukyu Islands, southwestern Japan, and a redescription of T. balli (McLaughlin & Haig, 1996) - Osawa, Masayuki; Fujita, Yoshihisa (Zootaxa, 2008)
Two new hermit crab species of the family Paguridae, Turleania saliens n. sp. and T. tenebrosa n. sp., are described from coral reefs of the Ryukyu Islands, southwestern Japan. Reexamination of the holotype of Turleania balli (McLaughlin & Haig, 1996) has shown that it has only nine pairs of quadriserial gills. This feature is also found in the two new species but does not fit with the original diagnosis of Turleania McLaughlin, 1997. Simple emendation of the genus Turleania is made for the number of gills to accommodate these three species. The two new species are quite similar to E. balli, but distinguished by the armature of the carpus of the right cheliped and anterior lobe of the sixth thoracic sternite. Turleania tenebrosa differs from T. saliens in the right chela having distinct spines on the dorsolateral surface, and meri of the second pereopods unarmed on the distal 0.3 of the ventral surface.